Y2O3-MgO ceramic and titanium alloy indirect brazing method

By preparing the Ag-CuO cladding layer on the surface of Y2O3-MgO ceramics and forming a TiO2 layer during vacuum brazing, the problem of poor bonding between Y2O3-MgO ceramics and titanium alloy brazing interface is solved, and a joint with high shear strength is achieved connect.

CN119426739AActive Publication Date: 2025-02-14HARBIN INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411370427.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-14
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

In the prior art, the brazing of Y2O3-MgO ceramics and titanium alloys has a problem of poor interface bonding, resulting in insufficient shear strength of the joints.

Method used

By using indirect brazing method, an Ag-CuO cladding layer was prepared on the surface of Y2O3-MgO ceramics to generate a reaction layer of Y2Cu2O5 and Mg0.8Cu0.2O to ensure good metallurgical bonding on the side interface of the ceramics. Then during the vacuum brazing process, the Ti elements in the titanium alloy diffuse and bind to the O atoms in the cladding layer to form a TiO2 layer, achieving good bonding of the entire interface.

Benefits of technology

The efficient connection between Y2O3-MgO ceramic and titanium alloy is achieved, and the shear strength of the obtained joint can reach 46MPa, which significantly improves the mechanical properties of the joint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119426739A_ABST
    Figure CN119426739A_ABST
Patent Text Reader

Abstract

The invention discloses an indirect brazing method for Y2O3-MgO ceramic and a titanium alloy, and relates to a brazing method for the Y2O3-MgO ceramic and the titanium alloy. The problem that interface bonding is poor when Y2O3-MgO ceramic and a metal material are brazed is solved. According to the method, firstly, the Ag-CuO cladding layer is prepared on the surface of the Y2O3-MgO ceramic, and the Y2Cu2O5 and Mg0. 8Cu0. 2O reaction layer is generated on the side interface of the ceramic, so that good metallurgical bonding of the side interface of the ceramic is ensured. And then in the vacuum brazing process, the Ti element in the titanium alloy can be diffused in the silver-based brazing filler metal, when the Ti element is diffused to the original cladding boundary, the Ti element is combined with O atoms decomposed from a cladding layer, and finally a TiO2 layer is formed on the original cladding boundary, so that reliable connection of a brazed joint is achieved. The shear strength of the obtained joint can reach 46 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a brazing method for Y2O3-MgO ceramics and titanium alloy. Background Art

[0002] Infrared windows are important components for the integration of high-speed aircraft structure and function. Currently, the main materials for infrared windows are sapphire, MgF2, etc., but they all have shortcomings. MgF2 has weak thermal shock resistance and cannot meet the future infrared window's requirements for high-temperature service environments; sapphire's self-radiation coefficient increases significantly at high temperatures, causing its own infrared signal to interfere with external signal reception. With the continuous development of infrared window materials, the new generation of infrared window materials Y2O3-MgO composite ceramics have gained widespread attention due to their low high-temperature self-radiation coefficient, good optical transmittance, mechanical strength and thermal shock resistance, and are expected to be used in high-speed drones and other fields in the future. The application of high-speed aircraft infrared windows often involves their connection with lightweight and high-strength titanium alloys, but due to the friction and impact of air during flight, higher requirements are placed on the mechanical properties and thermal shock resistance of the connection between the infrared window and the titanium alloy.

[0003] At present, there are few reports on the connection methods of Y2O3-MgO ceramics and titanium alloys. The connection between ceramic materials and metals usually adopts bolt connection, adhesive connection, brazing and other methods. Since it is difficult to process complete mechanical holes in Y2O3-MgO ceramics and the air tightness of the combination is poor, bolt connection is not suitable; although the adhesive method is simple, most ceramic and metal adhesive joints are prone to aging, and the joints have poor thermal shock resistance; vacuum brazing is suitable for connecting Y2O3-MgO ceramics and titanium alloys because of its high welding quality, high service temperature and long service life. However, due to the very stable chemical properties of Y2O3 and MgO, general metal brazing fillers cannot form a good bond with the ceramic interface. Summary of the invention

[0004] In order to solve the problem of poor interface bonding between Y2O3-MgO ceramics and metal materials during brazing, the present invention provides an indirect brazing method between Y2O3-MgO ceramics and titanium alloys.

[0005] The indirect brazing method of Y2O3-MgO ceramic and titanium alloy of the present invention is carried out according to the following steps:

[0006] 1. Pre-welding treatment of Y2O3-MgO ceramics:

[0007] The Y2O3-MgO ceramic is cut into predetermined sizes, and then the surface to be welded is polished step by step, ultrasonically cleaned and solvent cleaned in sequence;

[0008] 2. Pre-welding treatment of titanium alloy:

[0009] The titanium alloy is cut into predetermined sizes, and then the surface to be welded is polished, ultrasonically cleaned and solvent cleaned in sequence;

[0010] 3. Preparation of Ag-CuO cladding layer on Y2O3-MgO ceramic surface:

[0011] Ag powder and CuO powder are weighed, mixed and ground to obtain Ag-CuO cladding material, the Ag-CuO cladding material is dissolved in anhydrous ethanol to obtain Ag-CuO cladding slurry, and then the Ag-CuO cladding slurry is evenly coated on the surface of the Y2O3-MgO ceramic to be welded, and finally transferred to a muffle furnace for sintering;

[0012] The molar concentration of CuO in the Ag-CuO cladding material is 2-40%;

[0013] After the mixing, the mixture is ground for 5-30 minutes to obtain the Ag-CuO cladding material;

[0014] The mass fraction of the Ag-CuO cladding material in the Ag-CuO cladding slurry is 10-50%;

[0015] The sintering process is as follows: heating the temperature to 970-1100°C at a heating rate of 3-7°C / min, keeping the temperature for 10-30min, and cooling the temperature to room temperature at a cooling rate of 3-7°C / min; after sintering, CuO reacts with Y2O3 to generate Y2Cu2O5, and CuO reacts with MgO to generate Mg 0.8 Cu 0.2 O; to achieve good metallurgical bonding between the Y2O3-MgO ceramic side interface and the Ag-CuO cladding layer first, so as to achieve good overall bonding of the interface with the titanium alloy during the subsequent vacuum brazing process;

[0016] 4. Pre-treatment of silver-based solder foil:

[0017] Both surfaces of the silver-based solder foil were polished to remove the surface oxide film, followed by ultrasonic cleaning and solvent cleaning;

[0018] The solvent cleaning is performed by repeatedly cleaning with anhydrous ethanol or acetone 2 to 3 times;

[0019] 5. Assembly of welding specimens:

[0020] The silver-based solder foil is placed between the to-be-welded surface of the titanium alloy and the Ag-CuO cladding layer on the surface of the Y2O3-MgO ceramic, with the Ag-CuO cladding layer on the surface of the Y2O3-MgO ceramic facing downward, to obtain a to-be-welded component;

[0021] 6. Place the parts to be welded into a vacuum brazing furnace for vacuum brazing to complete the indirect brazing of Y2O3-MgO ceramics and titanium alloy;

[0022] The vacuum brazing process is as follows: under vacuum conditions, heating to 820°C to 900°C at a heating rate not exceeding 10°C / min and keeping the temperature for 10min to 40min, and then cooling to room temperature at a cooling rate not exceeding 10°C / min.

[0023] The principles and beneficial effects of the present invention are:

[0024] The present invention first prepares an Ag-CuO cladding layer on the surface of Y2O3-MgO ceramics, and generates Y2Cu2O5 and Mg on the ceramic side interface. 0.8 Cu 0.2 O reaction layer ensures good metallurgical bonding on the ceramic side interface. Then in the vacuum brazing process, the Ti element in the titanium alloy diffuses in the brazing material, and when it diffuses to the original cladding boundary, it combines with the O atoms decomposed in the cladding layer, and finally forms a TiO2 layer at the original cladding boundary, thereby achieving brazed joint connection. The shear strength of the resulting joint can reach 46MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a microstructure picture of the brazed joint of Y2O3-MgO ceramic and titanium alloy obtained in Example 1;

[0026] Figure 2 The microstructure picture of the brazed joint of Y2O3-MgO ceramic and titanium alloy obtained in Comparative Example 1;

[0027] Figure 3 This is a comparison chart of shear strength of brazed joints;

[0028] Figure 4 This is an elemental surface scanning image of the brazed joint of Y2O3-MgO ceramic and titanium alloy obtained in Example 1. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.

[0030] Specific implementation method 1: In this implementation method, the indirect brazing method of Y2O3-MgO ceramic and titanium alloy is carried out according to the following steps:

[0031] 1. Pre-welding treatment of Y2O3-MgO ceramics:

[0032] The Y2O3-MgO ceramic is cut into predetermined sizes, and then the surface to be welded is polished step by step, ultrasonically cleaned and solvent cleaned in sequence;

[0033] 2. Pre-welding treatment of titanium alloy:

[0034] The titanium alloy is cut into predetermined sizes, and then the surface to be welded is polished, ultrasonically cleaned and solvent cleaned in sequence;

[0035] 3. Preparation of Ag-CuO cladding layer on Y2O3-MgO ceramic surface:

[0036] Ag powder and CuO powder are weighed, mixed and ground to obtain Ag-CuO cladding material, the Ag-CuO cladding material is dissolved in anhydrous ethanol to obtain Ag-CuO cladding slurry, and then the Ag-CuO cladding slurry is evenly coated on the surface of the Y2O3-MgO ceramic to be welded, and finally transferred to a muffle furnace for sintering;

[0037] The molar concentration of CuO in the Ag-CuO cladding material is 2-40%;

[0038] After the mixing, the mixture is ground for 5-30 minutes to obtain the Ag-CuO cladding material;

[0039] The mass fraction of the Ag-CuO cladding material in the Ag-CuO cladding slurry is 10-50%;

[0040] The sintering process is as follows: heating the temperature to 970-1100°C at a heating rate of 3-7°C / min, keeping the temperature for 10-30min, and cooling the temperature to room temperature at a cooling rate of 3-7°C / min; after sintering, CuO reacts with Y2O3 to generate Y2Cu2O5, and CuO reacts with MgO to generate Mg 0.8 Cu 0.2 O; to achieve good metallurgical bonding between the Y2O3-MgO ceramic side interface and the Ag-CuO cladding layer first, so as to achieve good overall bonding of the interface with the titanium alloy during the subsequent vacuum brazing process;

[0041] 4. Pre-treatment of silver-based solder foil:

[0042] Both surfaces of the silver-based solder foil were polished to remove the surface oxide film, followed by ultrasonic cleaning and solvent cleaning;

[0043] The solvent cleaning is performed by repeatedly cleaning with anhydrous ethanol or acetone 2 to 3 times;

[0044] 5. Assembly of welding specimens:

[0045] The silver-based solder foil is placed between the to-be-welded surface of the titanium alloy and the Ag-CuO cladding layer on the surface of the Y2O3-MgO ceramic, with the Ag-CuO cladding layer on the surface of the Y2O3-MgO ceramic facing downward, to obtain a to-be-welded component;

[0046] 6. Place the parts to be welded into a vacuum brazing furnace for vacuum brazing to complete the indirect brazing of Y2O3-MgO ceramics and titanium alloy;

[0047] The vacuum brazing process is as follows: under vacuum conditions, heating to 820°C to 900°C at a heating rate not exceeding 10°C / min and keeping the temperature for 10min to 40min, and then cooling to room temperature at a cooling rate not exceeding 10°C / min.

[0048] This implementation has the following beneficial effects:

[0049] In this embodiment, a Ag-CuO cladding layer is first prepared on the surface of Y2O3-MgO ceramics, and Y2Cu2O5 and Mg are generated at the ceramic side interface. 0.8 Cu 0.2 O reaction layer ensures good metallurgical bonding on the ceramic side interface. Then in the vacuum brazing process, the Ti element in the titanium alloy diffuses in the brazing material, and when it diffuses to the original cladding boundary, it combines with the O atoms decomposed in the cladding layer, and finally forms a TiO2 layer at the original cladding boundary, thereby achieving brazed joint connection. The shear strength of the resulting joint can reach 46MPa.

[0050] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that: in step 1, 400-3000 mesh diamond sandpaper is used for the step-by-step grinding of the surface to be welded.

[0051] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that: the ultrasonic cleaning described in step one is carried out in an ultrasonic cleaning instrument, and the cleaning time is 10-20 minutes.

[0052] Specific implementation method 4: This implementation method is different from any one of specific implementation methods 1 to 3 in that: the solvent used in the solvent cleaning in step 1 is anhydrous ethanol or acetone.

[0053] Specific implementation method five: This implementation method is different from specific implementation methods one to four in that: in step two, 400-3000 mesh diamond sandpaper is used for the step-by-step grinding of the surface to be welded.

[0054] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that: the ultrasonic cleaning in step 2 is carried out in an ultrasonic cleaning instrument, and the cleaning time is 5-60 minutes.

[0055] Specific implementation method 7: This implementation method is different from any one of specific implementation methods 1 to 6 in that: the solvent used in the solvent cleaning in step 2 is anhydrous ethanol or acetone.

[0056] Specific implementation eight: This implementation differs from any one of specific implementations one to seven in that the titanium alloy described in step two is TC4 alloy.

[0057] Specific implementation method 9: This implementation method is different from any one of specific implementation methods 1 to 8 in that: in step 4, 400-3000 mesh sandpaper is used for grinding the two surfaces of the silver-based solder foil.

[0058] Specific implementation method ten: This implementation method is different from any one of specific implementation methods one to nine in that: the ultrasonic cleaning time in step four is 5-60 minutes.

[0059] Specific embodiment eleven: This embodiment differs from specific embodiments one to ten in that the silver-based solder foil is Ag-Cu solder foil, Ag-Cu-In solder foil, Ag-Cu-Ni solder foil or Ag-Cu-Ti solder foil.

[0060] Embodiment 1:

[0061] The indirect brazing method of Y2O3-MgO ceramic and titanium alloy in this embodiment is carried out according to the following steps:

[0062] 1. Pre-welding treatment of Y2O3-MgO ceramics:

[0063] The Y2O3-MgO ceramics were cut into samples of 4 mm × 4 mm × 3 mm, and then the surfaces to be welded were polished step by step, ultrasonically cleaned, and solvent cleaned in sequence;

[0064] The step-by-step grinding of the surface to be welded uses 400 mesh, 800 mesh, 1500 mesh, and 2000 mesh diamond sandpaper;

[0065] The ultrasonic cleaning is carried out in an ultrasonic cleaning instrument, and the cleaning time is 20 minutes;

[0066] The solvent used in the solvent cleaning is anhydrous ethanol;

[0067] 2. Pre-welding treatment of titanium alloy:

[0068] The titanium alloy was cut into specimens of 15 mm × 10 mm × 3 mm, and then the surface to be welded was polished, ultrasonically cleaned and solvent cleaned in sequence;

[0069] The step-by-step grinding of the surface to be welded uses 400 mesh, 800 mesh, and 1500 mesh diamond sandpaper;

[0070] The ultrasonic cleaning is carried out in an ultrasonic cleaning instrument, and the cleaning time is 20 minutes;

[0071] The solvent used in the solvent cleaning is anhydrous ethanol;

[0072] The titanium alloy is TC4 alloy;

[0073] 3. Preparation of Ag-CuO cladding layer on Y2O3-MgO ceramic surface:

[0074] Ag powder and CuO powder are weighed, mixed and ground to obtain Ag-CuO cladding material, the Ag-CuO cladding material is dissolved in anhydrous ethanol to obtain Ag-CuO cladding slurry, and then the Ag-CuO cladding slurry is evenly coated on the surface of the Y2O3-MgO ceramic to be welded, and finally transferred to a muffle furnace for sintering;

[0075] The molar concentration of CuO in the Ag-CuO cladding material is 8%;

[0076] The mixing is then ground for 20 minutes to obtain the Ag-CuO cladding material;

[0077] The mass fraction of the Ag-CuO cladding material in the Ag-CuO cladding slurry is 40%;

[0078] The sintering process is as follows: heating to 1000°C at a heating rate of 5°C / min, keeping the temperature for 30 minutes, and cooling to room temperature at a cooling rate of 5°C / min;

[0079] 4. Pre-treatment of Ag-Cu solder foil:

[0080] The two surfaces of the Ag-Cu solder foil were polished to remove the surface oxide film, and then ultrasonic cleaning was performed; the specification of the Ag-Cu solder foil was 6 mm×6 mm; the mass ratio of Ag to Cu in the Ag-Cu solder foil was 72:28;

[0081] The two surfaces of the Ag-Cu solder foil are polished with 1000-mesh sandpaper;

[0082] The mass ratio of Ag to Cu in the Ag-Cu solder foil is 72:28;

[0083] The ultrasonic cleaning time is 20 minutes; the frequency of the ultrasonic cleaning machine is 100kHz;

[0084] The solvent cleaning is repeated 3 times with anhydrous ethanol;

[0085] 5. Assembly of welding specimens:

[0086] The Ag-Cu solder foil is placed between the to-be-welded surface of the titanium alloy and the Ag-CuO cladding layer on the surface of the Y2O3-MgO ceramic, with the Ag-CuO cladding layer on the surface of the Y2O3-MgO ceramic facing downward, to obtain a to-be-welded part;

[0087] 6. Place the parts to be welded into a vacuum brazing furnace for vacuum brazing to complete the indirect brazing of Y2O3-MgO ceramics and titanium alloy;

[0088] The vacuum brazing process is as follows: under vacuum conditions, heating to 860° C. at a heating rate of 10° C. / min and keeping the temperature for 20 minutes, and then cooling to room temperature at a cooling rate of 5° C. / min.

[0089] Comparative Example 1:

[0090] The indirect brazing method of Y2O3-MgO ceramic and titanium alloy in this embodiment is carried out according to the following steps:

[0091] 1. Pre-welding treatment of Y2O3-MgO ceramics:

[0092] The Y2O3-MgO ceramics were cut into samples of 4 mm × 4 mm × 3 mm, and then the surfaces to be welded were polished step by step, ultrasonically cleaned, and solvent cleaned in sequence;

[0093] The step-by-step grinding of the surface to be welded uses 400 mesh, 800 mesh, 1500 mesh, and 2000 mesh diamond sandpaper;

[0094] The ultrasonic cleaning is carried out in an ultrasonic cleaning instrument, and the cleaning time is 20 minutes;

[0095] The solvent used in the solvent cleaning is anhydrous ethanol;

[0096] 2. Pre-welding treatment of titanium alloy:

[0097] The titanium alloy was cut into specimens of 15 mm × 10 mm × 3 mm, and then the surface to be welded was polished, ultrasonically cleaned and solvent cleaned in sequence;

[0098] The step-by-step grinding of the surface to be welded uses 400 mesh, 800 mesh, and 1500 mesh diamond sandpaper;

[0099] The ultrasonic cleaning is carried out in an ultrasonic cleaning instrument, and the cleaning time is 20 minutes;

[0100] The solvent used in the solvent cleaning is anhydrous ethanol;

[0101] The titanium alloy is TC4 alloy;

[0102] 3. Pre-treatment of Ag-Cu solder foil:

[0103] The two surfaces of the Ag-Cu solder foil were polished to remove the surface oxide film, and then ultrasonic cleaning was performed; the specification of the Ag-Cu solder foil was 6 mm×6 mm; the mass ratio of Ag to Cu in the Ag-Cu solder foil was 72:28;

[0104] The two surfaces of the Ag-Cu solder foil are polished with 1000-mesh sandpaper;

[0105] The mass ratio of Ag to Cu in the Ag-Cu solder foil is 72:28;

[0106] The ultrasonic cleaning time is 20 minutes; the frequency of the ultrasonic cleaning machine is 100kHz;

[0107] The solvent cleaning is repeated 3 times with anhydrous ethanol;

[0108] 4. Assembly of welding specimens:

[0109] Placing the Ag-Cu solder foil between the to-be-welded surface of the titanium alloy and the Ag-CuO cladding layer on the surface of the Y2O3-MgO ceramic to obtain a to-be-welded part;

[0110] 5. Place the parts to be welded into a vacuum brazing furnace for vacuum brazing to complete the indirect brazing of Y2O3-MgO ceramics and titanium alloy;

[0111] The vacuum brazing process is as follows: under vacuum conditions, heating to 860° C. at a heating rate of 10° C. / min and keeping the temperature for 20 minutes, and then cooling to room temperature at a cooling rate of 5° C. / min.

[0112] The shear test was carried out using an electronic universal testing machine with a loading speed of 0.5 mm / min. The room temperature shear strength of the connection joint obtained in Example 1 reached 46 MPa. Figure 1 This is a microstructure picture of the brazed joint of Y2O3-MgO ceramic and titanium alloy obtained in Example 1;

[0113] Figure 4 Table 1 is the element surface scan of the brazed joint of Y2O3-MgO ceramic and titanium alloy obtained in Example 1; Table 1 is the EDS analysis results of each phase in Example 1. Figure 1 , Figure 4 As shown in Table 1, in Example 1, a Ag-CuO cladding layer was first prepared on the surface of Y2O3-MgO ceramics, and Y2Cu2O5 and Mg 0.8 Cu 0.2 O reaction layer ensures good metallurgical bonding on the ceramic side interface. Then in the vacuum brazing process, the Ti element in the titanium alloy diffuses in the brazing material, and when it diffuses to the original cladding boundary, it combines with the O atoms decomposed in the cladding layer, and finally forms a TiO2 layer at the original cladding boundary, thereby achieving brazing joint connection.

[0114] Table 1

[0115]

[0116] The shear test was carried out using an electronic universal testing machine with a loading speed of 0.5 mm / min. The room temperature shear strength of the connection joint obtained in Comparative Example 1 reached 22 MPa. Figure 2 The microstructure picture of the brazed joint of Y2O3-MgO ceramic and titanium alloy obtained in Comparative Example 1; Figure 2 As shown, there are a large number of unwelded areas on the ceramic side interface of Comparative Example 1. This is because the reaction between Ag-Cu and Y2O3-MgO ceramic is very weak, and then under the action of large residual stress, through cracks are formed on the Y2O3-MgO ceramic side. This is because the reaction between Ag-Cu and Y2O3-MgO ceramic is very weak, and then under the action of large residual stress, the reaction interface on the Y2O3-MgO ceramic side cracks, and the obtained joint shear strength is relatively small.

[0117] Figure 3 The figure is a comparison chart of shear strength of brazed joints. Since the interface of the Y2O3-MgO ceramic with Ag-CuO cladding layer in Example 1 and the TC4 brazed joint is well bonded, the shear strength of the joint is increased by 109% compared with that of the comparative example 1 without cladding layer.

Claims

1. A method for indirect brazing of Y2O3-MgO ceramics and titanium alloys, characterized in that: The indirect brazing method of Y2O3-MgO ceramic and titanium alloy is carried out according to the following steps:

1. Pre-welding treatment of Y2O3-MgO ceramics: The Y2O3-MgO ceramic is cut into predetermined sizes, and then the surface to be welded is polished step by step, ultrasonically cleaned and solvent cleaned in sequence; 2. Pre-welding treatment of titanium alloy: The titanium alloy is cut into predetermined sizes, and then the surface to be welded is polished, ultrasonically cleaned and solvent cleaned in sequence; 3. Preparation of Ag-CuO cladding layer on Y2O3-MgO ceramic surface: Ag powder and CuO powder are weighed, mixed and ground to obtain Ag-CuO cladding material, the Ag-CuO cladding material is dissolved in anhydrous ethanol to obtain Ag-CuO cladding slurry, and then the Ag-CuO cladding slurry is evenly coated on the surface of the Y2O3-MgO ceramic to be welded, and finally transferred to a muffle furnace for sintering; The molar concentration of CuO in the Ag-CuO cladding material is 2-40%; After the mixing, the mixture is ground for 5-30 minutes to obtain the Ag-CuO cladding material; The mass fraction of the Ag-CuO cladding material in the Ag-CuO cladding slurry is 10-50%; The sintering process is as follows: heating the temperature to 970-1100°C at a heating rate of 3-7°C / min, keeping the temperature for 10-30min, and cooling the temperature to room temperature at a cooling rate of 3-7°C / min; after sintering, CuO reacts with Y2O3 to generate Y2Cu2O5, and CuO reacts with MgO to generate Mg 0.8 Cu 0.2 O; to achieve good metallurgical bonding between the Y2O3-MgO ceramic side interface and the Ag-CuO cladding layer first, so as to achieve good overall bonding of the interface with the titanium alloy during the subsequent vacuum brazing process; 4. Pre-treatment of silver-based solder foil: Both surfaces of the silver-based solder foil were polished to remove the surface oxide film, followed by ultrasonic cleaning and solvent cleaning; The solvent cleaning is performed by repeatedly cleaning with anhydrous ethanol or acetone 2 to 3 times; 5. Assembly of welding specimens: The silver-based solder foil is placed between the to-be-welded surface of the titanium alloy and the Ag-CuO cladding layer on the surface of the Y2O3-MgO ceramic, with the Ag-CuO cladding layer on the surface of the Y2O3-MgO ceramic facing downward, to obtain a to-be-welded component; 6. Place the parts to be welded into a vacuum brazing furnace for vacuum brazing to complete the indirect brazing of Y2O3-MgO ceramics and titanium alloy; The vacuum brazing process is as follows: under vacuum conditions, heating to 820°C to 900°C at a heating rate not exceeding 10°C / min and keeping the temperature for 10min to 40min, and then cooling to room temperature at a cooling rate not exceeding 10°C / min.

2. The indirect brazing method of Y2O3-MgO ceramic and titanium alloy according to claim 1, characterized in that: In step 1, diamond sandpaper with a mesh size of 400 to 3000 is used for the step-by-step grinding of the surface to be welded.

3. The indirect brazing method of Y2O3-MgO ceramic and titanium alloy according to claim 1, characterized in that: The ultrasonic cleaning in step 1 is carried out in an ultrasonic cleaning instrument, and the cleaning time is 10-20 minutes.

4. The indirect brazing method of Y2O3-MgO ceramic and titanium alloy according to claim 1, characterized in that: The solvent used in the solvent cleaning in step 1 is anhydrous ethanol or acetone.

5. The indirect brazing method of Y2O3-MgO ceramic and titanium alloy according to claim 1, characterized in that: In step 2, diamond sandpaper with a mesh size of 400 to 3000 is used for the step-by-step grinding of the surface to be welded.

6. The indirect brazing method of Y2O3-MgO ceramic and titanium alloy according to claim 1, characterized in that: The ultrasonic cleaning in step 2 is carried out in an ultrasonic cleaning instrument, and the cleaning time is 5-60 minutes.

7. The indirect brazing method of Y2O3-MgO ceramic and titanium alloy according to claim 1, characterized in that: The solvent used in the solvent cleaning in step 2 is anhydrous ethanol or acetone.

8. The indirect brazing method of Y2O3-MgO ceramic and titanium alloy according to claim 1, characterized in that: The titanium alloy described in step 2 is TC4 alloy.

9. The indirect brazing method of Y2O3-MgO ceramic and titanium alloy according to claim 1, characterized in that: In step 4, the two surfaces of the silver-based solder foil are polished using 400-3000 grit sandpaper.

10. The indirect brazing method of Y2O3-MgO ceramic and titanium alloy according to claim 1, characterized in that: The ultrasonic cleaning time in step 4 is 5-60 minutes.

Citation Information

Patent Citations

  • Method for assisting air reaction brazing through titanium alloy surface aluminizing

    CN110653442A

  • Method for brazing Y2O3-MgO composite ceramic and metal by adopting TiZrNiCu active brazing filler metal

    CN117921118A

  • Method for brazing zinc sulfide ceramic and titanium alloy dissimilar materials

    CN118060649A

  • Method for brazed connection of Y2O3-MgO nano-composite ceramic and titanium alloy

    CN118492542A

  • Brazed lower vacuum housing for a dewar

    US5598966A